Desenvolvimento de material didático digital para apoio ao ensino de alunos maduros no PROEJA/CTISM - Souza, Lubia Telma Garcia Wustrow (2021)
The current study has been developed in conjunction with the Postgraduate Course in Professional and Technological Education of the Industrial Technical School, at the Federal University of Santa Maria, Academic Master's Degree, within the research line on Innovation for Professional and Technological Education. The overall objective of this project was developing digital teaching material for mature students in the context of professional education: EJA EPT (PROEJA). The contributions and impacts of such digital teaching materials on mature students enrolled in this education modality have been discussed in view of the gaps left in their learning over time, throughout the history of Brazilian education. The relevance of this work is justified by the need to experiment different teaching materials with an adult and mature audience, through a qualitative research methodology applied and focused on the difficulties present in educational institutions. This research was dedicated to the development of a website, as well as teaching materials designed to assist PROEJA’s teachers and students. The data was collected through a survey applied to a sample of teachers working in this teaching modality and based on their pedagogical practices. The whole research resulted in a product with social and educational relevance, in support to the EJA EPT(PROEJA) teaching modality, fostering new perspectives in relation to this important public policy, especially in this current moment of so many adversities imposed by the Covid-19 pandemic, contributing to remote and hybrid teaching. In this way, the main objective of this work was achieved: an open educational product designed to assist PROEJA’s teachers in their classes, through the elaboration and availability of digital didactic materials for mature adult students, as well as the creation of an educational website to host the elaborated materials. The results obtained have also contributed to and expanded the possibilities for new research in the areas of active teaching methodologies for adults in EPT, such as research on the need of support for teachers working in basic education.